The Performance of Service Marketing Mix Towards Decision in Continuing Education at SMK Lugina Rancaekek, District of Bandung, West Java - Rachmawati, Mariana; Haizam Mohd Saudi, Mohd; Adjeng Mariana, R.; Adriansyah Anwar, Tezza (International Journal of Engineering and Technology, 2018)
This paper study on the effect of service marketing mix performance consisting of product, price, place, promotion, people, physical evidence, and process to decision in continuing education at SMK Lugina Rancaekek District of Bandung. The method used is quantitative method with descriptive approach. It used primary data and secondary data. This study was conducted in a field of education with population of all students of class X in SMK Lugina Rancaekek. Sample determination technique used is non-probability sampling technique with purposive sampling approach, which become sample in this research is class X student at SMK Lugina Rancaekek, that is 74 people. Data collection technique is done by questionnaire method, interview, observation, and documentation. Based on the results of study, with multiple regression analysis obtained value of 21,733. While, the correlation coefficient analysis is 0,607. The amount of influence of service marketing mix performance to decision in continuing education equal to 36,2% and the rest 63,8% influenced by other variable not examined in this study. T test results obtained t value arithmetic on product variables 2,516, price 2,618, place 2,565, promotion 1,999, people 2,577, physical evidence 2,066, and process 2,470 bigger than t table that is 1,9966, then Ha accepted and Ho rejected. Thus, it can be concluded that product variables, price, place, promotion, people, physical evidence, and process affect the decision in education in SMK Lugina Rancaekek.Â Â